1983
DOI: 10.1002/ajpa.1330610103
|View full text |Cite
|
Sign up to set email alerts
|

The dental morphology of Pima Indians

Abstract: Fourteen morphologic crown traits were observed in a sample of 1528 Pima Indians of south-central Arizona. Pima dentitions are characterized by high frequencies of shoveling, incisor winging, the hypocone, the lower canine distal accessory ridge, cusp 6, and the protostylid. They exhibit low frequencies of the metaconule and lower premolar multiple lingual cusps and moderate frequencies of the canine tubercle, Carabelli's trait, cusp 7, and lower second molars with four cusps and X groove patterns. When Pima c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 34 publications
2
39
0
1
Order By: Relevance
“…A lower MMD value indicates greater similarity and vice versa. It is assumed that phenetic similarity approximates cladistic relationship (Sokal and Sneath, 1963;Scott et al, 1983). Twenty-seven samples were compared on the basis of all 36 traits.…”
Section: Methodsmentioning
confidence: 99%
“…A lower MMD value indicates greater similarity and vice versa. It is assumed that phenetic similarity approximates cladistic relationship (Sokal and Sneath, 1963;Scott et al, 1983). Twenty-seven samples were compared on the basis of all 36 traits.…”
Section: Methodsmentioning
confidence: 99%
“…That is, the Mexican populations have more dental characters with frequencies similar to Sundadonts than Sinodonts, and overall they fit the Sundadont pattern described by Turner. Relative to other populations of American Indians (Dahlberg, 1949;Hrdlicka, 1931;Scott et al, 1983;, the Mesoamerican groups in this study have a low frequency of the almost universal trait for the Sinodont pattern, shoveling of upper incisors. This low frequency is also found in the Inuit of the Central Arctic (Mayhall, 1979).…”
Section: Monte Alban4mentioning
confidence: 76%
“…Previous studies have shown that American Indian populations follow the Sinodont pattern (Scott et al, 1983;Turner, 1983Turner, , 1985aTurner, , 1986a. The results of the discriminant analysis performed indicate that certain New World populations show frequencies of dental traits most consistent with the Sundadont pattern, suggesting extensive dental morphological variation among American Indians.…”
Section: Monte Alban4mentioning
confidence: 98%
See 1 more Smart Citation
“…The aetiology of the rotation could not be identified, as the patient did not have any orofacial deformities which are the possible aetiological factors for the presence of rotated tooth [6]. The clinical examinations of his parents and sibling did not reveal any malformed teeth.…”
Section: Discussionmentioning
confidence: 90%